Pilot study of an occupational healthcare program to assess the SARS-CoV-2 infection and immune status of employees in a large pharmaceutical company. (3rd June 2021) - Moroni-Zentgraf, Petra C.; Keller, Christoph; Mahmoudi, Mazyar; Kallsen, Kimberley; Eschenfelder, Christoph C.; Sigmund, Ralf; Müller, Hanns Walter; Baum, Patrick; Boos, Bertram; Schneider, Michael; Mundt, Egbert
Abstract: Objective: To safeguard key workers involved in development and production of medicines and ensure business continuity, we developed an occupational healthcare program, performed by our company's occupational healthcare services, to assess the infection and immune status for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This pilot program, conducted at our company facilities, evaluated the suitability of diagnostic tools in our setting for program upscaling. Methods: We used different marketed in vitro diagnostics (including tests for antibodies against spike protein subunits S1 and S2 and nucleocapsid [N] protein) combined with medical history, symptoms and likelihood of infection. We evaluated the testing strategy over four visits in 141 employees (known positive COVID-19 history, n  = 20; unknown status, n  = 121) between April and June 2020 at four company locations in Germany. Digital self-monitoring over the pilot program duration was also included. Results: No incident infections were detected. Based on immune status, medical history and likelihood of infection, 10 participants (8.3%) with previously unknown history of COVID-19 were identified to have been infected before entering the program. These participants, who recalled no or mild symptoms in the preceding months, were primarily identified using an assay that detected both S1 and S2 immunoglobulin (Ig) G. The frequency of positive lateral flow assay (LFA) results (IgM or IgG directed against the N-protein) in this cohort was lower compared with participants with a known history of COVID-19 (0‒10.8% vs. 33.8‒75.7%, respectively). Conclusions: Data from this pilot program suggest that LFA for antibodies may not always reliably detect current, recent or past infections; consequently, these have not been included in our upscaled occupational healthcare program. Regular testing strategies for viral RNA and antibodies directed against different SARS-CoV-2 proteins, combined with hygiene rules and a comprehensive baseline assessment, are recommended to ensure avoidance of infections at workplace as reliably as possible.